Cross-linking lignin and cellulose with polymers using siloxane compounds - Grade, Samantha; Zhang, Xavier; Yang, Che-Hao; Oduro, Isaac; Wang, Chenxi (Frontiers in Materials, 2024)
Siloxanes are a group of substances characterized by Si-O-Si functional group. Siloxanes can react with alcohols to form Si-O-C bond. Siloxanes have been widely used as crossing linking agents and graft copolymers as well as additives for plastics. Lignin contains both phenolic and aliphatic hydroxy groups which have the potential to instigate bonding with siloxane compounds. However, there has not been any attempt to apply siloxanes as crosslinking agents for biobased composite formation. This manuscript presents the first study of applying siloxanes compounds to lignin and Cellulose nanofibers (CNF) with respective PLA, PETG, and HDPE to prepare biocomposites. Both Tetramethyl Tetraphenyl Trisiloxane (TTT) and Tetraethoxysilane (TEOS) were used as cross-linking agents. We have successfully incorporated 20 wt% lignin and 10 wt% CNF into the biocomposite filaments. The tensile properties of ensuing biocomposite were investigated. The objective of this work is to demonstrate the potential of lignin and CNF as a sustainable co-polymer to improve the properties of PLA/PETG/HDPE-based materials for 3D printing. This paper will also discuss the challenges and opportunities associated with the use of lignin in 3D printing, including the effect of lignin and CNF content on the mechanical and thermal properties, the compatibility of lignin and CNF with PLA/PETG/HDPE, and the potential for further optimization of the cross-linking chemistry using TTT and TEOS.